In-situ synthesis of graphene encapsulated Fe/Fe2O3 nanoparticles for possible biomedical applications - Sıddıka Mertdinç-Ülküseven; Umut Savacı; Kubra Onbasli; Özge Balcı-Çağıran; Havva Yagci Acar; M. Lütfi Öveçoğlu; Duygu Ağaoğulları (Journal of Materials Research and Technology, 2022)
This paper reports on the in-situ synthesis, optimization, characterization and cytotoxicity tests of multi-layer graphene (MLG) encapsulated Fe/Fe2O3 nanoparticles (Fe/Fe2O3@C core–shell nanostructures) by spray drying-assisted chemical vapor deposition (CVD) using iron-nitrate/silica-based precursors. The influences of CVD reaction temperature, holding time, CH4/H2 gas flows and pressure on the synthesis of MLG encapsulated Fe/Fe2O3 nanoparticles were investigated. CVD-synthesized powders were purified using acid leaching to remove residual silica and probable uncoated Fe/Fe-oxide phases. XRD analyses revealed the presence of FCC (Fe,C), BCC Fe, graphite/graphene and trace amount of Fe2O3 phases. Raman spectra confirmed the existence of MLG shells. TEM indicated that MLG (from at least 3 to maximum of 35 layers) wrapped around the metallic cores ranged between 4 and 85 nm. Purification of nanoparticles did not degrade, dissolve or create discontinuity on the MLG structure. VSM measurements showed that nanoparticles obtained from the optimized conditions (900 °C, 100 ml/min CH4/H2, 50 mbar) had a soft ferromagnetic behavior with low saturation magnetization (∼85 emu/g) and coercivity (∼552 Oe) values. Optimized MLG encapsulated Fe/Fe2O3 nanoparticles were successfully suspended in water using a poly(acrylic acid) coating. Aqueous MLG encapsulated Fe/Fe2O3 nanoparticles were cytocompatible below 100 μg/ml at short incubation times, and showed the potential to be used in biomedical applications.